Between perfection and damnation: The emerging geography of markets - Cohen, Dan (Progress in Human Geography, 2018)
Economic geographers have recently taken up the study of markets after a long period of inattention. This growing literature has highlighted the diverse spaces, scales, and fields where markets are present, as well as the ways in which markets vary in form. However, the study of markets in economic geography still exists in tension between neoclassical and Marxist conceptions of markets as predictable and approaches like the social studies of economization/marketization which emphasize their contingency. This paper argues that work of Polyani and Gramsci can provide a way forward for the subfield through conceptualizing markets as sites of social struggle.
Geography
Keywords: capitalism; counterhegemony; earth scientists; economic geography; economic systems; geographers; human geography; marketization; markets; neoliberalism

Karl Polanyi as a spatial theorist - Roberts, Philip (Globalizations, 2018)
The ‘spatial’ turn in political economy has re-invigorated Marxian analysis, allowing for new research programmes into urbanization, geopolitics, and social movement activity amongst other topics. This tendency emerged through a critical re-reading of Marx and Gramsci, amongst others, uncovering spatial analyses embedded in the logic of their arguments. Conversely, Karl Polanyi’s interlocutors have tended to add geographical analysis as an additional layer of theory, reading space ‘in’ to the text. However, a close reading reveals that a concern with space permeates Polanyi’s analysis. As such, it is possible to read space ‘out’ of Polanyi, adding a level of theoretical rigour and logical consistency when applying his insights to geographic topics. This article carries out an exegesis of Karl Polanyi’s work, uncovering a theoretical framework that deals with space, place, scale, fixity, and motion. From this vantage point, the article considers the potential implications of this new geographical reading of Polanyi.
Geography
Keywords: Marxist philosophy; POLANYI; Karl; 1886-1964; capitalism; geography; international political economy; neoliberalism; scale; social sciences; space; spatial turn

Information Policy and the Spatial Constitution of Digital Geographic Information Markets - Alvarez León, Luis F. (Economic Geography, 2018)
Information policy has become one of the key instruments for the commodification and marketization of goods in contemporary capitalism. However, the spatializing role of this and other legal regimes has not been explored in depth. Among the categories of goods whose production and circulation is shaped by information policy, geographic information is increasingly salient in the digital economy due to the strategic and economic value derived from its integration of location and context. This article explores the role of information policy regimes in spatially bounding, structuring, and regulating digital geographic information markets. This is conducted through a Polanyian economic geographic approach that contextualizes, integrates, and synthesizes two types of geographic information market formations, and focuses on the institutional dimension of information policy regimes. In developing this approach, the article argues that legal regimes (in this case information policy) are capable of spatializing markets by structuring, integrating, and delimiting the actions of states and other actors, such as private corporations and consumers, within particular jurisdictions. The empirical section of the article illustrates this argument by showing how three aspects of information policy—(1) intellectual property, (2) infrastructure, and (3) commercialization—shape specific configurations of digital geographic information markets within the various administrative scales in the European Union, a globally influential jurisdiction for information policy, and where a regional digital market is in the process of construction. The article concludes by arguing that a Polanyian economic geographic approach provides a solid basis with ample versatility to account for the necessary integration of a legal perspective into the analysis of new kinds of goods (such as digital geographic information) and the spatialities of their emerging market configurations.
Geography
Keywords: United States; capitalism; digital economy; geographic information; geographic information systems; information markets; information policy; intellectual property; legal frameworks; prediction markets

Situated responses to the post‐political city: An introduction - Richter, Anna; Fitzpatrick, Susan (Area, 2018)
It seems with the ever more complex instituting of aggressive neoliberal renewal policies comes an intensified effort to use the language of consensus and civic unity. The post‐political debate frames this discussion, and it is from this perspective that we propose a fuller consideration of urban renewal policy, and how these forces are embedded within the narrowing of what has been called the “properly political”. In bringing together accounts of the dynamic political life of communities and groups of interest who are confronting urban renewal policy in Glasgow, we make a case for recognising an intensification of political articulation, position‐taking and action. This recognition comes in response to the argument that we are currently experiencing a post‐political consensus and that democracy has been annulled in the process. We see evidence of a Polanyian “double movement” in which the construction of consensual publics is such a marked characteristic across different accounts, and how this appears to have opened up new critical spaces of debate and action within the various communities of interest. We therefore openly question the post‐political as a condition, or a process, which seemingly unfolds unimpeded. We fear that “post‐political” runs the risk of becoming a citational practice, that through repetition of the term, a narrowing of political articulation and action within the debate starts to occur. Our case studies aim to highlight the blind spots of the post‐political debate by focusing on the actually existing spaces of political articulation and position‐taking apparent in Glasgow.
Geography
Keywords: Glasgow; articulation (speech); consensus (social sciences); debates & debating; political; urban policy; urban renewal